Clinical and genetic findings in autism spectrum disorders analyzed using exome sequencing - Blázquez, Ana; Rodriguez-Revenga, Laia; Alvarez-Mora, María I.; Calvo, Rosa (Frontiers in Psychiatry, 2025)
Autism spectrum disorder (ASD) refers to a group of complex neurodevelopmental disorders and is characterized by impaired reciprocal social interaction and communication, as well as the presence of restricted interests and stereotyped and repetitive behaviors. As a complex neurodevelopmental disorder, the phenotype and severity of autism are extremely heterogeneous, with differences from one patient to another. Chromosome microarray (CMA) and fragile X syndrome analyses has been used as a powerful tool to identify new candidate genes for ASD. Methods: In the present study, CMA was first used to scan for genome-wide copy number variants in the patient, and no clinically significant copy number variants were found. Exome sequencing (ES) was used for further genetic testing. Results: ES was performed on 20 subjects. Eighty percent of our sample presented intellectual disability. Other co-occurring clinical conditions included speech disorders, psychomotor delay, the presence of dysmorphic features and medical co-morbidities. A pathogenic variant was identified in 10 patients (ADNP, FBN1, WAC, ASXL3, NR4A2, ALX4, ANKRD1, POGZ, SHANK3 and BPTF). Patients with a positive finding in ES were more likely to present a dysmorphic trunk, more than three dysmorphic features, hypotonia, psychomotor delay and strabismus. Conclusions: ES offers expanded diagnostic options for patients with ASD who are negative on CMA. However, further studies are needed for a better understanding of ASD etiology and also the different phenotypes.